140: A Study of the Impact of Continuing Professional Development (CPD) Activities on Physicians' Knowledge, Motivation and Ability to Address Challenges with Exclusive Breastfeeding Practices. Issue 6 (1st June 2014) - Pound, C; Lindsay, E; Plint, AC; Moreau, K
Abstract: BACKGROUND: Physicians' attitudes and recommendations directly impact breastfeeding duration. Yet, Canadian primary care physicians are ill-equipped to support breastfeeding mothers as their confidence, attitudes and knowledge are known to be suboptimal. OBJECTIVES: This study aimed to develop, deliver, evaluate and refine a combination of continuing professional development (CPD) activities targeting specific gaps uncovered on a recent breastfeeding needs assessment of Canadian physicians, with the ultimate goal of encouraging study participants to integrate new skills and knowledge in their clinical practice. DESIGN/METHODS: We developed and delivered an interactive 90-minute workshop to facilitate physicians' ability to support patients' breastfeeding practices. The workshops were held at the Canadian Pediatric Society Annual Meeting in June 2012 in London, Ontario, at a continuing medical education event at the Children's Hospital of Eastern Ontario in November 2012, and at the Montfort Hospital in February 2013. Communication tools were distributed to improve information retention. Phone outreach was performed four to eight weeks post workshop to reinforce take-home messages from the workshop, gather information on the obstacles and challenges to implementing the various breastfeeding support practices provided at the workshop and to gather information regarding physicians' current perceptions and practices. Participation, participants' satisfaction with each element of the CPD activities and participants' learning were also tracked through the use of questionnaires and the follow-up phone outreach. We aimed to recruit 30 to 40 physicians. RESULTS: In total, seven physicians agreed to participate in the study. Workshop participation increased these participants' confidence levels in breastfeeding counseling skills (ie, latch evaluation, sore nipple complaints, milk transfer evaluation), improved their knowledge, and was associated with a desire to change their clinical practice. The workshop was overall rated as relevant, interesting, effective, and helpful. CONCLUSIONS: Physician recruitment was found to be much more difficult than anticipated, and a large selection bias was inevitable as only physicians with a keen interest in learning about breastfeeding participated in the study. However, our participants rated the intervention very positively. Given the difficulty in recruitment, a more feasible approach needs to be adapted and evaluated. In future, the intervention will be targeted at residency level.